Propuesta de Máster Plan del Vacío Urbano de la Actual SENAGUA Riobamba - Sánchez Chávez, Melany Nicole (2023)
Urban voids are part of the city's resources that are wasted, they have great potential to be used if they are articulated to the city, this is the case study of this research project that focuses on the urban void. of the current Secretaria Nacional del Agua (SENAGUA), currently this site generates several urban problems such as fragmenting the urban layout, pollution, insecurity, among others, in addition to the great physical barrier that it has become for the sector and the city. The proposal is based on the diagnosis of the site, complemented by the theoretical analysis and references that have been carried out, the proposal aims to turn the urban void into a compact node of mixed uses that helps the development of the sector, for this purpose, equipment has been proposed that makes lacking in the study area and which are also complemented with the existing ones, the facilities are based on the three axes that the author Richard Rogers talks about in his book "Cities for a small Planet" which are; work, housing and leisure. With the Master Plan proposal carried out in conjunction with the strategies and guidelines proposed, it is intended to articulate the study area with the city, helping the development of the sector and that this in turn helps to create a more compact and less dispersed city.